Compliance with Iron Tablet Consumption Can Affect the Incidence of Anemia During Pregnancy - Adinda Syaikha Luthfia Puteri; Wiwin Widayani; Rika Resmana; Chris Sriyanti (Jurnal Kebidanan, 2026)
Anemia during pregnancy, defined as hemoglobin levels below 11 g/dL, remains a significant health concern due to its association with postpartum hemorrhage, preterm birth, and low birth weight. One contributing factor is the low adherence to iron tablet (Fe) supplementation, despite widespread distribution programs. This study aimed to analyze the relationship between adherence to iron tablet consumption and the incidence of anemia among third-trimester pregnant women at Jatinangor Public Health Center. A case-control design was employed, involving 82 respondents, 41 anemic (case group) and 41 non-anemics (control group), selected through simple random sampling. Data were analyzed using Chi-Square tests and odds ratio (OR) calculations. The results showed that 56.1% of pregnant women were classified as non-adherent. A significant relationship was found between adherence to iron tablet consumption and anemia incidence (p = 0.000), with an OR of 15.909 (95% CI: 5.254–48.169), indicating that non-adherent mothers had a 15.9-fold higher risk of developing anemia. Adherence was influenced not only by quantity but also by timing, method of consumption, and maternal understanding. Barriers such as side effects, incorrect consumption habits, and low family involvement were also identified. These findings highlight the need for enhanced health education, greater family engagement, and continuous monitoring to improve adherence to iron tablet supplementation and support anemia prevention among pregnant women.